Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/aur.1822
|View full text |Cite
|
Sign up to set email alerts
|

Associations of endocrine stress‐related gene polymorphisms with risk of autism spectrum disorders: Evidence from an integrated meta‐analysis

Abstract: Our results showed no evidence of significant association of either COMT rs4680 or 5-HTT 5-HTTLPR variants with ASD, showing that these two genes may not be major susceptible genetic factors in ASD occurrence, and may have a reciprocal action with each other in combination with environmental factors. These findings further provide evidence that a single gene variant may not dictate autism occurrence, but possibly contributes to a specific phenotype or subtype of ASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 132 publications
(171 reference statements)
1
8
0
Order By: Relevance
“…Out of the remaining six articles, two were already in our dataset from the literature search from PubMed. Finally, four articles from the GWAS catalog were manually added to 27 articles previously screened from PubMed, leading to a total of 31 eligible articles [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] being included in the systematic review ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Out of the remaining six articles, two were already in our dataset from the literature search from PubMed. Finally, four articles from the GWAS catalog were manually added to 27 articles previously screened from PubMed, leading to a total of 31 eligible articles [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] being included in the systematic review ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The role of 5-HTTLPR polymorphism in the ASD pathophysiology evaluated through case-control studies and family-based association have reflected conflicting results. For instance, two studies suggested S allele as risk variant for ASD [ 15 , 16 ], while three meta-analysis did not find association [ 26 28 ]. We assessed this polymorphism through a case-control approach failing to find association between 5-HTTLPR and idiopathic ASD, and also through a family-based assessment that did not find a preferential transmission of either S or L allele.…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing the under-representation of Latin American population in studies aimed to understand the role of 5-HTTLPR on worldwide [26,27,29], here we present a meta-analysis including articles which evaluate this polymorphism in Latin American individuals with psychiatric disorders as ASD, bipolar disorder, major depressive disorder, obsessive compulsive disorder, attention deficit hyperactive disorder, schizophrenia, dysthymia, anxiety disorder and suicide [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. Although the S allele has been associated with increased risk for psychiatric disorders [16][17][18][19][20][21]55], our meta-analysis revealed no significant heterogeneity among studies, no publication bias and failed to find an association between 5-HTTLPR and a risk for psychiatric disorders.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, they reported only two population-based studies and a formal meta-analysis of these studies could not be done. Moreover, Yang et al found 5-HTTLPR polymorphism did not significantly affect ASD risk based on six case-control studies with obvious heterogeneity (22). However, more population-based studies explored the effect of 5-HTTLPR polymorphism on autism risk but the results were still not consistent and remained inconclusive.…”
Section: Introductionmentioning
confidence: 99%